low-cost plastic rain-shelter and poly-tunnel for protected vegetable cultivation in high rainfall - Singh, Raghuveer; Kalita, H; Angami, T; Makdoh, B; Touthang, L (Indian Horticulture, 2023)
The actual problem of low productivity of vegetables in Arunachal Pradesh has been attributed to the extremes of rainfall (2,500 mm) and 142 rainy days, which prohibits year-round vegetable cultivation at large scale. This difficulty is also an opportunity of growing vegetable crops in protected cultivation and the area under protected cultivation is growing larger day-by-day and now farmers can cultivate in off-season with the induction of an artificial technique like low-cost plastic rain-shelter and poly-tunnel.